The relationship between CSR and financial performance: Evidence from Chinese listed firms - Liu, Zhiyi (2019)
In recent decades, the implementation of social responsibility activities has increasingly attracted the attention of enterprises and the public. Western academic communities have arisen attention and research on corporate social responsibility for a long time. The rich empirical research on the relationship between corporate social responsibility (CSR) and financial performance (CFP) has generally shown that the excellent social performance of enterprises will improve its profitability. Compared with western countries, market economy in China develops late, and corporate maturity is relatively low. The focus on social responsibility is still in its infancy, and the theoretical and empirical research on the relationship between CSR and CFP is relatively rare. This paper starts from the concept of corporate social performance and detect the potential relationship between CSR and CFP through the empirical research.